Vascular disorders of liver tumors - Davidenko, Nicolás; Casanova, Marys; Silva García, Ernesto; Curuchet, Eduardo; Alba, Walter; D'St´efanis, Eduardo (Cirugía del Uruguay, 1977)
Fifty angiograms of hepatic tumors corresponding to 36 patients with primitive and secondary tumors, were reviewed: 20 were oleohepatographies, 16 liver arteriographies. 14 autopsy livers were treated by postmortem injection which permited microangiographic study of tumors in 11 cases. Ali parts were examined microscopically. _In the case of 20 patients and in 2 post-morteros examinations, the portal venous system . was studied (by trans-splenic and trans-umbilical injection in the case of the former, and in the latter by injection in the trunk). No venous penetration of tumoral area was found, whether the tumors were primitive or secondary. 27 arteriographies were performed: 16 "in vivo" and 11 injections in anatomical parts. In 13 cases ( 48,15 % ) the tumoral nade was hypervascularized; in 4 clinical cases ( 14,81 % ) indirect signs of tumor existence were observed: arterial infiltration and stretching. 10 cases (37,03 % ) were avascular. In all post-mortems hypervascularized and avascularized nades co-existed, thus forming a mixed radiological type. The absence of radiological and macroscopic arterial irrigation of sorne nades, does not mean that a vascular network did not exist. Histological examination showed the presence of a few vessels and the fibrous transformation of tumor, possibly connected with inmunobiological phenomena.